Comparison of Echocardiographic Measures in a Hispanic/Latino Population With the 2005 and 2015 American Society of Echocardiography Reference Limits (The Echocardiographic Study of Latinos). (January 2016) - Qureshi, Waqas T.; Leigh, J. Adam; Swett, Katrina; Dharod, Ajay; Allison, Matthew A.; Cai, Jianwen; Gonzalez, Franklyn; Hurwitz, Barry E.; Shah, Sanjiv J.; Desai, Ankit A.; Spevack, Daniel M.; Rodriguez, Carlos J.
Abstract : Background—: Reference limits for echocardiographic quantification of cardiac chambers in Hispanics are not well studied. Methods and Results—: We examined the reference values of left atrium and left ventricle (LV) structure in a large ethnically diverse Hispanic cohort. Two-dimensional transthoracic echocardiography was performed in 1818 participants of the Echocardiographic Study of Latinos (ECHO-SOL). Individuals with body mass index ≥30 kg/m 2, hypertension, diabetes mellitus, coronary artery disease, and atrial fibrillation were excluded leaving 525 participants defined as healthy reference cohort. We estimated 95th weighted percentiles of LV end systolic volume, LV end diastolic volume, relative wall and septal thickness, LV mass, and left atrial volume. We then used upper reference limits of the 2005 and 2015 American Society of Echocardiography (ASE) and 95th percentile of reference cohort to classify the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) target population into abnormal and normal. Reference limits were also calculated for each of 6 Hispanic origins. Using ASE 2015 defined reference values, we categorized 7%, 21%, 57%, and 17% of men and 18%, 29%, 60%, and 26% of women as having abnormal LV mass index, relative, septal, and posterior wall thickness, respectively. Conversely, 10% and 11% of men and 4% and 2% of women were classified as having abnormal end-diastolic volume and internal diameter by ASE 2015 cutoffs, respectively. Similar differences were found when we used 2005 ASE cutoffs. Several differences were noted in distribution of cardiac structure and volumes among various Hispanic/Latino origins. Cubans had highest values of echocardiographic measures, and Central Americans had the lowest. Conclusions—: This is the first large study that provides normal reference values for cardiac structure. It further demonstrates that a considerable segment of Hispanic/Latinos residing in the United States may be classified as having abnormal measures of cardiac chambers when 2015 and 2005 ASE reference cutoffs are used.